A neoschumpeterian review of the impact of corruption on competitiveness and foreign direct investment - Berumen, Sergio A.; HEGEMANN, Petra (Papeles de Europa, 2011)
In countries where the government encourages “donations” and “gifts” from private companies, FDI firms are more likely than their domestic counterparts to engage in corrupt forms of political influence, known as State Captures. Different types of foreign investors engage in particular types of corruption, depending on what competitive advantage they will get out of it. FDI firms with local partners are more likely to engage in State Capture. Larger multinational firms with headquarters overseas rely much less on State Capture, yet are more likely to resort to political corruption and bribery, Kickbacks, in their dealing with foreign governments. Though quite often, foreign direct investors might claim that they are specifically targeted for bribes by local governments, it has been found that there is no evidence that FDI firms pay higher overall bribes than domestic firms, even though they are more likely to engage in specific forms of corruption.